2013
DOI: 10.1038/jid.2012.284
|View full text |Cite
|
Sign up to set email alerts
|

Update of Immune Events in the Murine Contact Hypersensitivity Model: Toward the Understanding of Allergic Contact Dermatitis

Abstract: Allergic contact dermatitis (ACD) is one of the most common skin diseases, consisting of sensitization and elicitation phases. With the advancement of technology and the discovery of new types of immune cells, our knowledge of the immunological mechanisms of contact hypersensitivity (CHS) as a murine model of ACD has expanded significantly in the past decade. For example, by introducing regulatory T cells, CD4(+) T-helper 17 cells, and Langerin-positive dermal dendritic cells, the initiation and termination me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
379
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 329 publications
(395 citation statements)
references
References 127 publications
(131 reference statements)
3
379
1
12
Order By: Relevance
“…Previous in vivo and in vitro studies demonstrated that haptens activate skin cells and induce the production of several cytokines including IL-1b that stimulates the migration of skin dendritic cells to the lymph nodes and has a key role in contact dermatitis [27]. Hapten-induced effects mediated by innate immune systems are essential for the activation of cutaneous antigen-presenting cells [28]. Indeed, the innate immunity response is a prerequisite for the activation of the ACD immune response [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo and in vitro studies demonstrated that haptens activate skin cells and induce the production of several cytokines including IL-1b that stimulates the migration of skin dendritic cells to the lymph nodes and has a key role in contact dermatitis [27]. Hapten-induced effects mediated by innate immune systems are essential for the activation of cutaneous antigen-presenting cells [28]. Indeed, the innate immunity response is a prerequisite for the activation of the ACD immune response [29].…”
Section: Discussionmentioning
confidence: 99%
“…We first examined the effect of RvE1 in the sensitization phase of CHS because dermal DC migration to dLNs is an essential step for sensitization (Honda et al, 2013). WT mice treated with RvE1 exhibited a significantly reduced number of CD44 + CD62L + central memory T cells and CD44 + CD62L  effector memory T cells in dLNs after 0.5% 2,4-dinitrofluorobenzene (DNFB) application (Fig.…”
Section: Rve1 Inhibits DC Migration From Skin To Dlnsmentioning
confidence: 99%
“…In this study, we investigated the effects and underlying mechanisms of RvE1 on DC motility using a CHS model, which is a prototype of delayed-type hypersensitivity in the skin mediated by IFN- (Mori et al, 2008;Honda et al, 2013). RvE1 inhibited cutaneous DC migration into the dLNs and suppressed antigen-specific T cell induction in the sensitization phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ey dominate in the skin during the early phase of contact dermatitis [83]. 2 cells play a central role in allergic disorders such as AD by regulating both acute-and late-phase allergic reactions, mediated by immunoglobulin E and eosinophils, re-spectively.…”
Section: T Cells T Cells In Their Naive State Rst Encounter Apcs In Smentioning
confidence: 99%